2010
DOI: 10.1063/1.3323108
|View full text |Cite
|
Sign up to set email alerts
|

Engineering directed excitonic energy transfer

Abstract: We provide an intuitive platform for engineering exciton transfer dynamics. We show that careful consideration of the spectral density, which describes the system-bath interaction, leads to opportunities to engineer the transfer of an exciton. Since excitons in nanostructures are proposed for use in quantum information processing and artificial photosynthetic designs, our approach paves the way for engineering a wide range of desired exciton dynamics. We carefully describe the validity of the model and use exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…Very different population relaxation dynamics depending on the construction of the bath spectral density suggests that some of the phenomenology can be described poorly by a bath that is incorrectly parameterized, i.e., the description of open quantum dynamics in vibronic systems may need to be supported by good computational studies to determine system-specific parameters. This sensitive behavior also indicates another possibility of controlling system dynamics by modulating the system-bath interaction, which is in line with the previous studies, 56,87 in addition to controlling it by an external field. 88 …”
Section: Intramolecular Vibrational Relaxationsupporting
confidence: 74%
“…Very different population relaxation dynamics depending on the construction of the bath spectral density suggests that some of the phenomenology can be described poorly by a bath that is incorrectly parameterized, i.e., the description of open quantum dynamics in vibronic systems may need to be supported by good computational studies to determine system-specific parameters. This sensitive behavior also indicates another possibility of controlling system dynamics by modulating the system-bath interaction, which is in line with the previous studies, 56,87 in addition to controlling it by an external field. 88 …”
Section: Intramolecular Vibrational Relaxationsupporting
confidence: 74%
“…Although we are particularly motivated by the need to understand excitonic energy transfer in photosynthetic light-harvesting complexes, our model is general-transport in a tight-binding system with dephasing, a source and a trap-and can be expected to have wider application.Recent experimental studies of photosynthetic light-harvesting complexes have confronted us with the fact that at least some of these systems exhibit excitonic coherence that is surprisingly long considering their noisy environment [1][2][3]. This makes it clear that if we are to understand their high light-harvesting efficiency, we must study the ways in which quantum transport is affected by the interplay of coherence and noise [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It has been found that noise can enhance quantum transport in model excitonic Hamiltonians [4][5][6], a phenomenon called environmentassisted quantum transport (ENAQT) or decoherence-assisted transport.In the simplest approach, different environments around each chromophore lead to a tightbinding model with sites that have different energies (disorder).…”
mentioning
confidence: 99%
“…It seems that the high efficiency of the light conversion is related to these coherent properties, which are quantum in nature. Therefore, the physical mechanism of photosynthesis assisted by quantum coherence has generated much experimental [3][4][5][6] and theoretical [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] research. An inherent mechanism for high-efficiency energy transfer is, to our best knowledge, still unknown.…”
Section: Introductionmentioning
confidence: 99%